2019
DOI: 10.3390/children6040053
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Renal Replacement Therapy with High Flow Rate Can Effectively, Safely, and Quickly Reduce Plasma Ammonia and Leucine Levels in Children

Abstract: Introduction: Peritoneal dialysis and continuous renal replacement therapy (CRRT) are the most frequently used treatment modalities for acute kidney injury. CRRT is currently being used for the treatment of several non-renal indications, such as congenital metabolic diseases. CRRT can efficiently remove toxic metabolites and reverse the neurological symptoms quickly. However, there is not enough data for CRRT in children with metabolic diseases. Therefore, we aimed a retrospective study to describe the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Although CRRT is a life-saving treatment, complications such as circuit clotting, hypothermia, hypotension, anemia, thrombocytopenia and electrolyte disturbances may occur during the treatment [22], with anemia and thrombocytopenia being common complications in neonates [23]. In a single-center retrospective study by Akduman [24], the incidence of thrombocytopenia was 62.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Although CRRT is a life-saving treatment, complications such as circuit clotting, hypothermia, hypotension, anemia, thrombocytopenia and electrolyte disturbances may occur during the treatment [22], with anemia and thrombocytopenia being common complications in neonates [23]. In a single-center retrospective study by Akduman [24], the incidence of thrombocytopenia was 62.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, CKRT has emerged as an essential approach to treating acute metabolic crises in children [ 15 ], and experience in the use of CKRT in infants weighing 10 kg or less has improved [ 16 ]. There have, however, been only a limited number of studies evaluating CKRT in patients diagnosed with IEM to date [ 6 8 , 15 ]. The primary strength of the present study is its status as the study with the most extensive CKRT series (28 sessions) in patients diagnosed with IEM to date, and the fact that more than half of the patients (15 patients 53.6%) were under the age of 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no current recommended level for starting extracorporeal detoxification for the management of hyperleucinemia, it is known that CKRT may be required if leucine levels exceed 1500 μmol/L [ 17 ]. Aygun et al reported an initial mean leucine level in patients with MSUD of 1777 ± 831.6 μmol/L [ 6 ], while another study reported an initial leucine level of 1648 ± 623.8 μmol/L [ 7 ]. In the present study, the mean initial plasma leucine level value was 1608 ± 885.3 μmol/L, and the initial plasma leucine levels of nine patients were < 1500 μmol/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the cerebral oedema is due to the neurotoxicity associated with accumulation of the ketoacids and leucine, CVVHDF was commenced on day 3 to assist with clearance of these metabolites. [3][4][5][6][7][8] Nutritional management. The patient's baseline weight (53 kg) and height (1.51 m) were in the normal range (body mass index 23 kg/m 2 ).…”
Section: Key Aspects Of Her Managementmentioning
confidence: 99%